Strategies to Improve Employee Performance through Effective Leadership and a Healthy Culture - Musa, Maman; Angriani, Rini; Akadji, Irfan; Syamsinah, Syamsinah; Wahdah, Ghoriqna Fibachril (Westscience Press, 2024)
This article discusses strategies for improving employee performance through effective leadership and a healthy organizational culture. In the context of a competitive world of work, the role of leadership is crucial in creating a work environment that supports motivation and productivity. This study identifies leadership characteristics that contribute to the development of a positive organizational culture, such as openness, good communication, and recognition of employee achievements. In addition, this article also explores how a healthy organizational culture, characterized by values of collaboration and trust, can improve job satisfaction and, ultimately, employee performance. Through the analysis of the review literature, this article provides practical recommendations for managers and leaders to implement effective strategies in improving employee performance.